Al2O3-10 wt% Fe composite prepared by high energy ball milling: Structure and magnetic properties. Issue 1 (1st January 2021) - Raimundo, Rafael A.; Reinaldo, Rayanne S.S.; Câmara, Nailton T.; Lourenço, Cleber S.; Costa, Franciné A.; Macedo, Daniel A.; Gomes, Uílame U.; Morales, Marco A.
Abstract: In the present work, Al2 O3 -10 wt% Fe composite powders were manufactured by mechanical alloy using different milling times. The morphology, structure and magnetic properties were carefully investigated and explained through the results of SEM, XRD (with Rietveld refinement), Mössbauer spectroscopy and magnetic measurements at low-temperatures. After 50 h of milling, the results reveal α-Fe particles uniformly distributed in Al2 O3 and a decrease of the average particle size of Al2 O3 –Fe composite. Besides, XRD data show a decrease of crystallite sizes, accompanied by an increase of the lattice micro-strain. For samples milled for 30 h and 50 h, the Mössbauer spectra recorded at 300 K showed a superparamagnetic component related to very fine hematite crystallites with a maximum absorption relative area of 10%. The M − H curves recorded at 6 K showed a small reduction in saturation magnetization, and an improvement in remanence magnetization and coercivity field with milling time, while the M-T curve of the sample milled for 50 h shows a peak at 185 K, related to the Morin transition of the hematite phase. Highlights: Al2 O3 -10 wt% Fe composite prepared by High Energy Milling (HEM). Due to milling the α-Fe particles are transformed into plates and fine Al2 O3 particles are deposited on their surface. The samples milled for 30 and 50 h have hematite superparamagnetic nanoparticles. The hematite has a Morin transition at 185 K.